2021
DOI: 10.3390/microorganisms9030537
|View full text |Cite
|
Sign up to set email alerts
|

High Prevalence of Carbapenemase-Producing Acinetobacter baumannii in Wound Infections, Ghana, 2017/2018

Abstract: Three years after a prospective study on wound infections in a rural hospital in Ghana revealed no emergence of carbapenem-resistant bacteria we initiated a new study to assess the prevalence of multidrug-resistant pathogens. Three hundred and one samples of patients with wound infections were analysed for the presence of resistant bacteria in the period August 2017 till March 2018. Carbapenem-resistant Acinetobacter (A.) baumannii were further characterized by resistance gene sequencing, PCR-based bacterial s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 44 publications
0
11
0
Order By: Relevance
“…In Ghana specifically, several studies exist on phenotypic and molecular characterization of these priority pathogens mainly with a focus on clinical isolates. Intermediate to high rates of resistance to cephalosporins and carbapenems similar to estimates in the continent and globally were reported in these studies despite limitations of small sample sizes in some cases [ 25 33 ]. With regards to surveillance of AMR from hospital environments, research studies exist [ 34 37 ] but are inadequate especially for Gram-negative pathogens considering the important role hospital environments can play in transmission.…”
Section: Introductionmentioning
confidence: 57%
See 1 more Smart Citation
“…In Ghana specifically, several studies exist on phenotypic and molecular characterization of these priority pathogens mainly with a focus on clinical isolates. Intermediate to high rates of resistance to cephalosporins and carbapenems similar to estimates in the continent and globally were reported in these studies despite limitations of small sample sizes in some cases [ 25 33 ]. With regards to surveillance of AMR from hospital environments, research studies exist [ 34 37 ] but are inadequate especially for Gram-negative pathogens considering the important role hospital environments can play in transmission.…”
Section: Introductionmentioning
confidence: 57%
“…performed a study in a tertiary care hospital in Nepal whereby 232 samples were collected from various sites and Acinetobacter species were the most prevalent GNB [ 68 ], and Aliramezani et al detected clonal expansion of CRAB in hospital environments in Iran [ 69 ]. There are limited published data available from Africa, however high emerging prevalence of carbapenemase A. baumannii has been documented in wound infections in Ghana [ 32 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…blaOXA-58 had not previously been reported in Nigeria, and blaOXA-23 has been reported in only two Nigerian studies (15,16). The blaOXA-420 variant of the blaOXA-58 family detected in one isolate has been reported in A. baumannii in only a handful of studies, including two conducted in neighboring Ghana (47)(48)(49). blaNDM-1, which is a less commonly described but highly potent carbapenem resistance gene in A. baumannii, was present in over a third of the isolates, four of which also co-carried blaOXA-23 (50).…”
Section: Discussionmentioning
confidence: 97%
“…In this study considerable resistance (70% ->90%) against cephalosporins, fluoroquinolones, cotrimoxazoles, piperacillin/tazobactam, carbapenems, amikacin and ampicillin/sulbactam was revealed. Currently the therapeutic options for CRAB might be cefiderocol or colistin in combination with carbapenems or minocycline or tigecycline (Monnheimer et al, 2021). The study showed appreciable invitro activity of tigecycline (44.39%), minocycline (85.96%), polymyxin B (89.89%) and colistin (97.48%) against CRAB isolates, the use of which could be rationalized for the most effective management of these isolates.…”
Section: Discussionmentioning
confidence: 95%